2010
DOI: 10.18632/oncotarget.205
|View full text |Cite
|
Sign up to set email alerts
|

miR-101 is down-regulated in glioblastoma resulting in EZH2-induced proliferation, migration, and angiogenesis

Abstract: Background Glioblastoma (GBM) is a malignant brain tumor with dismal prognosis. GBM patients have a median survival of less than 2 years. GBM is characterized by fast cell proliferation, infiltrative migration, and by the induction of angiogenesis. MicroRNAs and polycomb group (PcG) proteins have emerged as important regulators of gene expression. Methods Here we determined that miR-101 is down-regulated in GBM, resulting in overexpression of the miR-101 target PcG protein EZH2, a histone methyltransferase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
152
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(162 citation statements)
references
References 45 publications
9
152
1
Order By: Relevance
“…These investigations focused mainly on two aspects: impact of microRNA expression on glioma-associated ECs, such as miR-125b (Smits et al 2012), miR-296 (Wurdinger et al 2008), and miR-101 (Smits et al 2010), and microRNA expression in glioma cells and function in angiogenesis. For instance, miRNA-26a has been shown to act as an oncogene and promote glioma angiogenesis, while miR-128 suppresses gliomal growth and angiogenesis through targeting p70S6K1 (Qian et al 2013;Shi et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These investigations focused mainly on two aspects: impact of microRNA expression on glioma-associated ECs, such as miR-125b (Smits et al 2012), miR-296 (Wurdinger et al 2008), and miR-101 (Smits et al 2010), and microRNA expression in glioma cells and function in angiogenesis. For instance, miRNA-26a has been shown to act as an oncogene and promote glioma angiogenesis, while miR-128 suppresses gliomal growth and angiogenesis through targeting p70S6K1 (Qian et al 2013;Shi et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…EZH2 has been shown to regulate cancer angiogenesis (22, 24). We determined whether KSHV-induced up-regulation of EZH2 contributed to KSHV-induced angiogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, mutation of EZH2 Y641, which results in gain-of-function, has been described in lymphomas (21). Recent studies have shown that both VEGF and FGF2 induce angiogenesis through up-regulation of EZH2 expression, and inhibition of EZH2 attenuated the cell proliferation, migration and tubule formation of Glioblastoma cells (18, 2224). …”
Section: Introductionmentioning
confidence: 99%
“…Quantitative PCR and immunohistochemistry demonstrated that EZH2 is more expressed in GBMs than in low-grade gliomas [33]. EZH2 expression was detected in tumor cells by immunohistochemistry in GBM samples; no detectable expression was observed in adjacent brain parenchyma [33,35,54]. The TCGA data analysis revealed that other PcG genes are commonly overexpressed in GBMs.…”
Section: H3k27me3mentioning
confidence: 98%
“…Immunocytochemical studies showed that the number of tumor cells with nuclear localization of EZH2 is greater around tumor vessels and at the invasive front in human glioma specimens [53]. Silencing of EZH2 expression led to cell cycle arrest, decrease in cell proliferation, invasion and angiogenesis, and induced apoptosis in vitro [37,[54][55][56][57] and in vivo [53,54]. Pharmacological inhibition of EZH2 function with 3-deazaneplanocin A (DZNep) induced transcriptome changes consistent with the EZH2 role as a repressor of gene expression.…”
Section: H3k27me3mentioning
confidence: 99%